Comparison among plaque assay, tissue culture infectious dose (TCID) 50 and real-time RT-PCR for SARS-CoV-2 variants quantification (2022)
ABSTRACT: SARS-CoV-2 variants of concern (VOC) and interest (VOI) pose a significant threat to pub lic health because the rapid change in the SARS-CoV-2 genome can alter viral phenotypes such as virulence, transmissi bility and the ability to evade the host response. Hence, SARS-CoV-2 quantification techniques are essential for timely diagnosis and follow-up. Besides, they are vital to understanding viral pathogenesis, antiviral evaluation, and vaccine de velopment. Materials and Methods: Five isolates of SARS-CoV-2: D614G strain (B.1), three VOC (Alpha, Gamma and Delta), and one VOI (Mu) were used to compare three techniques for viral quantification, plaque assay, median tissue culture infectious dose (TCID ) and real-time RT-PCR. Results: Plaque assay showed viral titers between 0.15 ± 0.01×107 and 1.95 ± 0.09×107 PFU/mL while viral titer by TCID assay was between 0.71 ± 0.01×106 to 4.94 ± 0.80×106 TCID /mL for the five SARS-CoV-2 isolates. The PFU/mL titer obtained by plaque and the calculated from TCID assays differed by 0.61 log10, 0.59 log10, 0.59 log10 and 0.96 log10 for Alfa, Gamma, Delta, and Mu variants (p≤0.0007), respectively. No differences were observed for the D614G strain. Real-time PCR assay exhibited titers ranging from 0.39 ± 0.001×108 to 3.38 ± 0.04×108 RNA copies/µL for all variants. The relation between PFU/mL and RNA copies/mL was 1:29800 for D614G strain, 1:11700 for Alpha, 1:8930 for Gamma,1:12500 for Delta, and 1:2950 for Mu.Conclusion: TCID assay was comparable to plaque assay for D614G but not for others SARS-CoV-2 variants. Our data demonstrated a correlation among PFU/mL and E gene RNA copies/µL, units of measure commonly used to quantify the viral load in diagnostic and research fields. The results suggest that the proportion of infectious virions in vitro changes de pending on the SARS-CoV-2 variant, being Mu, the variant reaching a higher viral titer with fewer viral copies.